Preparation method of two-component polysaccharide / polyethylene glycol solid-solid phase change material based on freeze-drying self-packaging

Through lyophilized self-packaging technology, combining alginate and cellulose salt and polyethylene glycol, a porous foam material with high phase change enthalpy is prepared, solving the problems of low heat storage density and leakage of traditional solid-solid phase change materials, and achieving efficient thermal energy storage and release.

CN119709129APending Publication Date: 2025-03-28INNER MONGOLIA UNIV OF SCI & TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510221419.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-27
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The low heat storage density of traditional solid-solid phase change materials leads to leakage problems during thermal energy storage and release, and physical or chemical modification methods have limited impact on the thermal stability of polyethylene glycol.

Method used

By lyophilized self-encapsulation technology, hydrogels were prepared by sol-gel method using alginate and cellulose salts as encapsulation materials, and a porous foam material with high phase change enthalpy was obtained by lyophilization and molding.

Benefits of technology

It realizes efficient packaging of phase change materials, avoids leakage problems during phase change, and improves the latent heat and heat storage density of phase change, ensuring the shape stability and thermal stability of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119709129A_ABST
    Figure CN119709129A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a two-component polysaccharide / polyethylene glycol solid-solid phase change material based on freeze-drying self-packaging, which comprises the following steps: preparing hydrogel from alginate as a packaging material, cellulose salt as a reinforcing agent and polyethylene glycol through a sol-gel method; then, a porous foam material with high phase change enthalpy is obtained through a freeze-drying packaging technology, and finally, the solid-solid phase change material compact in texture is obtained through compression molding. The preparation method is simple, the process is easy to control, the used raw materials are wide in source, non-toxic and degradable, the prepared phase change material has a skeleton-like core-shell structure, the leakage problem of the phase change material in the phase change process can be effectively solved, and the phase change material is high in latent heat and good in heat storage and shaping effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of phase change materials and relates to a preparation method of a two-component polysaccharide / polyethylene glycol solid-solid phase change material based on freeze-drying self-encapsulation. Background Art

[0002] Thermal energy plays an important role in the development of human economic society. At present, the utilization of renewable thermal energy is still limited. A large amount of heat is wasted in the environment during the conversion process. Thermal storage technology can solve the imbalance of energy in time and space and improve energy utilization efficiency. Phase change thermal storage materials have high heat storage density and constant working temperature, and have irreplaceable advantages in practical application fields. According to the phase change mode of phase change thermal storage materials, they can be mainly divided into solid-solid phase change materials, solid-liquid phase change materials and liquid-gas phase change materials. Among them, the first two materials are more widely used because of their small volume changes during the phase change process. Solid-solid phase change materials mainly realize the storage and release of thermal energy through the change of crystal form. No liquid is produced during the phase change process. Compared with solid-liquid phase change materials, there is no leakage problem. At the same time, the material is non-toxic and non-corrosive, has a long service life, and has broad application prospects. However, the heat storage density of traditional solid-solid phase change materials has the disadvantage of low energy storage density compared with solid-liquid phase change materials. The development of new process methods to prepare solid-solid phase change materials with high energy storage density has become the focus of the industry and technology.

[0003] At present, the development of new solid-solid phase change materials mainly focuses on obtaining energy storage materials that exhibit solid-solid phase change, have good mechanical properties, and are easy to process and shape by physically or chemically modifying solid-liquid phase change materials with good performance. At present, among many small molecules, polymers and inorganic salt phase change materials, polyethylene glycol is widely studied. Polyethylene glycol has high latent heat of phase change and is green and environmentally friendly, making it an ideal solid-liquid phase change material. The strategies to improve the high-temperature shape stability of polyethylene glycol mainly include two categories: one is physical encapsulation, including encapsulation using organic, inorganic high specific surface area porous materials or polymer microcapsules; the other is chemical grafting, block copolymerization and chemical cross-linking of polyethylene glycol by chemical methods. However, during the physical encapsulation process, mechanical processing will damage the polyethylene glycol molecular chain and affect its thermal stability, and it is prone to leakage, which limits its practical application in various fields; chemical grafting or block copolymerization will limit the freedom of movement of polyethylene glycol segments, affecting its crystallization process and phase change behavior.

[0004] Based on this, the present invention aims to obtain a solid-solid phase change material through self-packaging, which can effectively avoid leakage of the phase change material, improve the shape stability of the phase change material, and obtain extremely high latent heat of phase change. Summary of the invention

[0005] In view of the above technical problems, the present invention aims to provide a method for preparing a two-component polysaccharide / polyethylene glycol solid-solid phase change material based on freeze-drying self-encapsulation. In the method, alginate is used as an encapsulation material, cellulose salt is used as an enhancer, and polyethylene glycol is prepared by a sol-gel method to obtain a hydrogel, and then a porous foam material with a high phase change enthalpy is obtained by freeze-drying encapsulation technology, and finally a solid-solid phase change material with a tight texture is obtained by molding. The preparation method of the present invention is simple, the process is easy to control, the raw materials used are widely available and are non-toxic and degradable, the prepared phase change material has a bone-like core-shell structure, which can effectively solve the leakage problem of the phase change material during the phase change process, and the phase change material has high latent heat, and good heat storage and shaping effects.

[0006] To achieve the above object, the technical solution adopted by the present invention is: A method for preparing a two-component polysaccharide / polyethylene glycol solid-solid phase change material based on freeze-drying self-encapsulation is carried out in the following steps in sequence: S1. Preparation of multi-component hydrogels After adding alginate and cellulose salt into water and mixing evenly, polyethylene glycol is added thereto, and after stirring at 50°C for 1 h, a 1.2 mol / mL hydrochloric acid solution is added, and the pH value of the solution is adjusted to 3-5, and then the solution is aged at 40°C for 6-48 h to obtain a multi-component hydrogel; S2. Preparation of porous foam Freezing and cooling the multi-component hydrogel and then freeze-drying it to obtain a porous foam material; S3. Preparation of solid-solid phase change materials 0.1-0.2 g of the porous foam material was placed in a cylindrical metal mold with a diameter of 13 mm and pressed to obtain a two-component polysaccharide / polyethylene glycol solid-solid phase change material.

[0007] In the present invention, the pH value of the solution system directly affects the formation of the hydrogel and the strength of the cross-linked structure of the polysaccharide. The adjustment of the pH value will affect the molecular conformation of the charged polysaccharide and the electrostatic interaction of the molecules, thereby affecting the pore structure, specific surface area and mechanical properties of the porous foam, and further affecting the self-encapsulation effect. In addition, the cross-linking density of the hydrogel will be affected by the aging time. When the aging time is 6-48 h, a three-dimensional hydrogel structure will be slowly formed. If the aging time is less than 6 h, the degree of cross-linking of the polysaccharide will be insufficient, resulting in the collapse of the three-dimensional hydrogel structure. If the aging time is greater than 48 h, the product will not be cured well, thereby affecting the formation of the three-dimensional structure of the hydrogel.

[0008] As a limitation of the preparation method of the present invention, in step S1, the alginate is one or more of sodium alginate, potassium alginate, and calcium alginate; and the cellulose salt is sodium carboxymethyl cellulose or potassium carboxymethyl cellulose.

[0009] As another limitation of the preparation method of the present invention, in step S1, the molecular weight of the polyethylene glycol is 2000-10000.

[0010] As a third limitation of the preparation method of the present invention, in step S1, the mass ratio of alginate to cellulose salt, water and polyethylene glycol is 1: (0.01-0.5): (20-100): (5-9).

[0011] In the present invention, the mass ratio of alginate to cellulose salt, water and polyethylene glycol affects the three-dimensional structure of the hydrogel, the self-encapsulation structure in the porous foam and the aggregation form of polyethylene glycol. Alginate and cellulose salt will be cross-linked under acidic conditions to form a three-dimensional structure, and this three-dimensional structure will self-encapsulate the polyethylene glycol. As the content of polyethylene glycol increases, the effect of alginate on the crystallization of polyethylene glycol is weakened, thereby affecting the phase change enthalpy of the solid-solid phase change material. At the same time, the increase of cellulose salt will increase the cross-linking strength of the hydrogel, thereby increasing the leakage-proof effect of the phase change material and the thermal stability of cyclic use.

[0012] As a fourth limitation of the preparation method of the present invention, in step S2, the freezing and cooling is performed according to the following procedure: (a) In the first cooling stage, the temperature was lowered from room temperature to 0 °C at a cooling rate of 0.3 °C / min and kept at this temperature for 6 h; (b) The second cooling stage: the temperature was lowered from 0°C to -20°C at a cooling rate of 0.1°C / min and kept warm for 18 h.

[0013] In the present invention, the hydrogel freezing and cooling procedure has a direct impact on the formation of porous foam material crystals, the coating of polyethylene glycol by two-component polysaccharides, and the formation and morphology of the complete core-shell structure. When the temperature is cooled from room temperature to 0°C at a cooling rate of 0.3°C / min, the volume of the hydrogel will expand slightly. If the cooling rate is less than 0.3°C / min, it will increase energy consumption and time cost. If the cooling rate is greater than 0.3°C / min, the expansion rate will be too fast and the three-dimensional structure of the hydrogel will be destroyed. The purpose of keeping warm for 6 hours is to allow the hydrogel to have enough time to adjust the internal molecular arrangement structure at around 0°C to avoid freezing too quickly to form a large internal stress. When the temperature is cooled from 0°C to -20°C at a cooling rate of 0.1°C / min, water molecules begin to form ice crystals. If the cooling rate is less than 0.1°C / min, the ice crystals will be too small, the sublimation channel will become narrow and reduce production efficiency. If the cooling rate is greater than 0.1°C / min, the water molecules will be rapidly overcooled to form overly large ice crystals, destroying the three-dimensional structure of the hydrogel. h is to ensure that the water molecules of the hydrogel completely form ice crystals.

[0014] As a fifth limitation of the preparation method of the present invention, it is characterized in that, in step S2, the freeze-drying temperature is -60°C and the time is 20-60 h.

[0015] In the present invention, the freeze-drying process is accompanied by the migration and volatilization of water molecules. When the drying temperature is -60°C, it can ensure that water is fully crystallized in preparation for sublimation. Drying for 20-60 h can make the ice crystals of the hydrogel fully sublime, and finally form a skeleton-like core-shell structure, thereby affecting the water content and the skeleton-like core-shell structure of the porous foam material.

[0016] As a sixth limitation of the preparation method of the present invention, in step S3, the pressing process is: firstly applying a load of 1-2 MPa for pre-pressing, then applying a load of 5-10 MPa for pressing, and maintaining the pressure for 10-50 s.

[0017] In the present invention, the porous foam material needs to be pre-pressed and initially formed at a relatively low pressure. If the pressure is greater than 2 MPa, a portion of the air will be enclosed in the test piece, resulting in cracks that are easy to form during tableting. If the pressure is less than 1 MPa, insufficient air will be discharged, ultimately resulting in the material being not dense enough. Then, a suitable pressure is further applied to ensure that the shape of the solid-solid phase change material finally formed is stable and has a certain mechanical strength, while maintaining good thermal conductivity and packaging effects, ensuring that the skeletal core-shell structure will not be destroyed due to excessive pressure. If the pressure is greater than 10 MPa, the sample will rupture. If the pressure is less than 5 MPa, the tablet will not be formed into a shape.

[0018] The present invention uses polyethylene glycol as a phase change energy storage material, selects two-component sugars as packaging materials and reinforcing materials, prepares a multi-component porous foam through a gentle and simple preparation process, and forms a final solid-solid phase change material through compression molding. The solid-solid phase change material has a bone-like core-shell structure, which can effectively inhibit the leakage of the phase change material during the phase change process. In addition, the exoskeleton layer is composed of alginate and cellulose salt, and polyethylene glycol is encapsulated in the inner skeleton layer to form bone marrow to prevent leakage. At the same time, this bone-like structure has a good communication channel, which facilitates the crystal growth of polyethylene glycol, so the solid-solid phase change material has an extremely high phase change latent heat.

[0019] The above technical solution of the present invention is taken as a whole, and each step is closely related and influences each other, which jointly determine the morphological characteristics and performance of the product.

[0020] The above technical solution has the following advantages or beneficial effects: 1. In the freeze-drying process of the present invention, the two-component polysaccharide can realize self-encapsulation of polyethylene glycol, and the prepared phase change material has a skeleton-like core-shell structure, and has extremely high encapsulation efficiency and loading rate, heat storage and shaping effects; 2. The raw materials used in the present invention are widely available. Alginate, cellulose salt and polyethylene glycol are all biocompatible, non-toxic and degradable, and have low cost, which meets the requirements of relevant industries for green environmental protection and sustainable development; 3. The preparation method of the present invention is simple, the process is easy to control, and it is easy to industrialize production.

[0021] The invention is suitable for preparing a two-component polysaccharide / polyethylene glycol solid-solid phase change material based on freeze-drying self-encapsulation.

[0022] The technical solution of the present invention will be further described in detail below in conjunction with the accompanying drawings and specific implementation methods. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 The physical pictures of the phase change material prepared in Example 5 of the present invention, wherein: (a) is a physical picture of a porous foam material, and (b) is a physical picture of a solid-solid phase change material formed by tableting; Figure 2 Leakage test diagrams of the phase change materials prepared in Examples 1-5 and Comparative Examples 1-2 of the present invention at 100° C. for different time periods; Figure 3 The scanning electron microscope images of the porous foam prepared in Example 5 of the present invention, wherein: (a) is a scanning electron microscope image of the core-shell structure, and (b) is a schematic diagram of the microscopic morphology; Figure 4The differential scanning calorimetry curves of the phase change materials prepared in Examples 1-5 and Comparative Examples 1-6 of the present invention are shown in FIG. 1 , wherein: (a) is a temperature rise diagram of Examples 1-5, (b) is a temperature drop diagram of Examples 1-5, (c) is a temperature rise diagram of Comparative Examples 1-6, and (d) is a temperature drop diagram of Comparative Examples 1-6; Figure 5 This is a differential scanning calorimetry curve of the solid-solid phase change material prepared in Example 5 of the present invention before and after 2000 thermal cycles. DETAILED DESCRIPTION

[0024] The following embodiments are only some embodiments of the present invention, rather than all embodiments. Therefore, the detailed description in the embodiments of the present invention provided below is not intended to limit the scope of the present invention claimed for protection, but merely represents selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without making creative work belong to the protection scope of the present invention.

[0025] In the present invention, unless otherwise specified, all equipment and raw materials can be purchased from the market or are commonly used in the industry. The methods in the following embodiments are all conventional methods in the art unless otherwise specified. Example 1

[0026] This example prepares a two-component polysaccharide / polyethylene glycol solid-solid phase change material based on freeze-drying self-encapsulation, and the preparation process and steps are as follows: S1. Preparation of multi-component hydrogels Sodium alginate and sodium carboxymethyl cellulose are added to water and mixed evenly, and then polyethylene glycol with a molecular weight of 2000-10000 is added, wherein the mass ratio of alginate to sodium carboxymethyl cellulose, water, and polyethylene glycol is 1:0.01:100:5, and after stirring at 50°C for 1 hour, a 1.2 mol / mL hydrochloric acid solution is added, and the pH of the solution is adjusted to 3, and then matured at 40°C for 6 hours to obtain a multi-component hydrogel; S2. Preparation of porous foam material The multi-component hydrogel was placed in a programmed cooling apparatus, first cooled from room temperature to 0°C at a cooling rate of 0.3°C / min, kept warm for 6 h, then cooled from 0°C to -20°C at a cooling rate of 0.1°C / min, kept warm for 18 h, and then freeze-dried at -60°C for 20 h to obtain a porous foam material; S3. Preparation of solid-solid phase change materials 0.1 g of porous foam material was placed in a cylindrical metal mold with a diameter of 13 mm, and then a load of 2 MPa was applied for pre-compression, and then a load of 10 MPa was applied for compression, and the pressure was maintained for 20 s to obtain a solid-solid phase change material. Example 2

[0027] This example prepares a two-component polysaccharide / polyethylene glycol solid-solid phase change material based on freeze-drying self-encapsulation, and the preparation process and steps are as follows: S1. Preparation of multi-component hydrogels Potassium alginate and potassium carboxymethyl cellulose are added to water and mixed evenly, and then polyethylene glycol with a molecular weight of 2000-10000 is added, wherein the mass ratio of alginate to sodium carboxymethyl cellulose, water, and polyethylene glycol is 1:0.05:80:6, and after stirring at 50°C for 1 h, a 1.2 mol / mL hydrochloric acid solution is added, and the pH of the solution is adjusted to 4, and then matured at 40°C for 12 h to obtain a multi-component hydrogel; S2. Preparation of porous foam material The multi-component hydrogel was placed in a programmed cooling apparatus, first cooled from room temperature to 0°C at a cooling rate of 0.3°C / min, kept warm for 6 h, then cooled from 0°C to -20°C at a cooling rate of 0.1°C / min, kept warm for 18 h, and then freeze-dried at -60°C for 40 h to obtain a porous foam material; S3. Preparation of solid-solid phase change materials 0.15 g of porous foam material was placed in a cylindrical metal mold with a diameter of 13 mm, and then a load of 1.5 MPa was applied for pre-compression, and then a load of 8 MPa was applied for compression, and the pressure was maintained for 10 s to obtain a solid-solid phase change material. Example 3

[0028] This example prepares a two-component polysaccharide / polyethylene glycol solid-solid phase change material based on freeze-drying self-encapsulation, and the preparation process and steps are as follows: S1. Preparation of multi-component hydrogels Potassium alginate and potassium carboxymethyl cellulose are added to water and mixed evenly, and then polyethylene glycol with a molecular weight of 2000-10000 is added, wherein the mass ratio of alginate to sodium carboxymethyl cellulose, water, and polyethylene glycol is 1:0.1:60:7, and after stirring at 50°C for 1 hour, a 1.2 mol / mL hydrochloric acid solution is added, and the pH of the solution is adjusted to 5, and then matured at 40°C for 24 hours to obtain a multi-component hydrogel; S2. Preparation of porous foam material The multi-component hydrogel was placed in a programmed cooling apparatus, first cooled from room temperature to 0°C at a cooling rate of 0.3°C / min, kept warm for 6 h, then cooled from 0°C to -20°C at a cooling rate of 0.1°C / min, kept warm for 18 h, and then freeze-dried at -60°C for 60 h to obtain a porous foam material. S3. Preparation of solid-solid phase change materials 0.2 g of porous foam material was placed in a cylindrical metal mold with a diameter of 13 mm, and then a load of 1 MPa was applied for pre-compression, and then a load of 5 MPa was applied for compression, and the pressure was maintained for 50 s to obtain a solid-solid phase change material. Example 4

[0029] This example prepares a two-component polysaccharide / polyethylene glycol solid-solid phase change material based on freeze-drying self-encapsulation, and the preparation process and steps are as follows: S1. Preparation of multi-component hydrogels Calcium alginate and potassium carboxymethyl cellulose are added to water and mixed evenly, and then polyethylene glycol with a molecular weight of 2000-10000 is added, wherein the mass ratio of alginate to sodium carboxymethyl cellulose, water, and polyethylene glycol is 1:0.25:40:8, and after stirring at 50°C for 1 hour, a 1.2 mol / mL hydrochloric acid solution is added, and the pH of the solution is adjusted to 4, and then matured at 40°C for 48 hours to obtain a multi-component hydrogel; S2. Preparation of porous foam material The multi-component hydrogel was placed in a programmed cooling apparatus, first cooled from room temperature to 0°C at a cooling rate of 0.3°C / min, kept warm for 6 h, then cooled from 0°C to -20°C at a cooling rate of 0.1°C / min, kept warm for 18 h, and then freeze-dried at -60°C for 50 h to obtain a porous foam material. S3. Preparation of solid-solid phase change materials 0.2 g of porous foam material was placed in a cylindrical metal mold with a diameter of 13 mm, and then a load of 1 MPa was applied for pre-compression, and then a load of 8 MPa was applied for compression, and the pressure was maintained for 50 s to obtain a solid-solid phase change material. Example 5

[0030] This example prepares a two-component polysaccharide / polyethylene glycol solid-solid phase change material based on freeze-drying self-encapsulation, and the preparation process and steps are as follows: S1. Preparation of multi-component hydrogels Potassium alginate and potassium carboxymethyl cellulose are added to water and mixed evenly, and then polyethylene glycol with a molecular weight of 2000-10000 is added, wherein the mass ratio of alginate to sodium carboxymethyl cellulose, water, and polyethylene glycol is 1:0.5:20:9, and after stirring at 50°C for 1 hour, a 1.2 mol / mL hydrochloric acid solution is added, and the pH of the solution is adjusted to 4, and then matured at 40°C for 48 hours to obtain a multi-component hydrogel; S2. Preparation of porous foam material The multi-component hydrogel was placed in a programmed cooling apparatus, first cooled from room temperature to 0°C at a cooling rate of 0.3°C / min, kept warm for 6 h, then cooled from 0°C to -20°C at a cooling rate of 0.1°C / min, kept warm for 18 h, and then freeze-dried at -60°C for 36 h to obtain a porous foam material. S3. Preparation of solid-solid phase change materials 0.1 g of porous foam material was placed in a cylindrical metal mold with a diameter of 13 mm, and then a load of 2 MPa was applied for pre-compression, and then a load of 8 MPa was applied for compression, and the pressure was maintained for 20 s to obtain a solid-solid phase change material. Comparative Example

[0031] In order to explore the effects of different parameters and different preparation processes in the preparation process of the present invention on the performance of the product of the present invention, the following comparative experiments were conducted. Different solid-solid phase change materials were prepared in the following comparative examples, as follows: Comparative Example 1 In this comparative example, a solid-solid phase change material is prepared. The preparation process is similar to that of Example 5, except that no two-component sugar is added and only polyethylene glycol phase change material is added.

[0032] Comparative Example 2 In this comparative example, a solid-solid phase change material is prepared. The preparation process is similar to that of Example 5, except that the polyethylene glycol is not encapsulated by preparing a hydrogel and a porous foam, but only by simple physical mixing. The specific steps are as follows: Sodium alginate was uniformly mixed with sodium carboxymethyl cellulose, water and polyethylene glycol in a mass ratio of 1:0.5:20:9, and 0.1 g was taken and placed in a cylindrical metal mold with a diameter of 13 mm. A load of 2 MPa was then applied for pre-compression, and then a load of 8 MPa was applied for compression. The pressure was maintained for 20 s to obtain a solid-solid phase change material.

[0033] Comparative Example 3 In this comparative example, a solid-solid phase change material is prepared. The preparation process is similar to that of Example 4, except that in step S1, only sodium alginate is added to encapsulate polyethylene glycol, and the remaining steps and parameters are the same as those of Example 4.

[0034] Comparative Example 4 In this comparative example, a solid-solid phase change material is prepared. The preparation process is similar to that of Example 4, except that in step S1, only sodium carboxymethyl cellulose is added to encapsulate polyethylene glycol, and the remaining steps and parameters are the same as those of Example 3.

[0035] Comparative Example 5 In this comparative example, a solid-solid phase change material is prepared. The preparation process is similar to that of Example 2, except that in step S1, the pH of the solution is adjusted to 7, and the remaining steps and parameters are the same as those of Example 2.

[0036] Comparative Example 6 In this comparative example, a solid-solid phase change material is prepared. The preparation process is similar to that of Example 1, except that in step S2, the temperature is directly cooled from room temperature to -20°C at a cooling rate of 0.3°C / min and kept warm for 18 h. The remaining steps and parameters are the same as those of Example 1. Performance Testing

[0037] The phase change materials prepared in Examples 1-5 and Comparative Examples 1-6 were characterized for their relevant properties, as follows: like Figure 1 , which are the physical pictures of the phase change material prepared in Example 1 of the present invention, where (a) is the physical picture of the porous foam material, and (b) is the physical picture of the solid-solid phase change material formed by tableting. It can be seen from the figure that the porous foam obtained by freeze-drying is a loose white block, and after molding, the phase change material obtained is a dense white cylindrical block. After calculation, the density of the porous foam is 0.15g / cm 3 -0.20g / cm 3 The final density of the solid-solid phase change material is 1.1 g / cm 3 -1.5g / cm 3 .

[0038] like Figure 2 , which are leakage test diagrams of the phase change materials prepared by Examples 1-5 and Comparative Examples 1-2 of the present invention at different times at 100°C. It can be seen from the diagram that the phase change material prepared by Comparative Examples 1-2 melts quickly at 100°C, while the solid-solid phase change material prepared by Example 1-5 does not melt, which indicates that Example 1-5 has a good anti-leakage effect.

[0039] like Figure 3 , which are scanning electron microscope images of the porous foam prepared in Example 5 of the present invention, wherein (a) is a scanning electron microscope image of the core-shell structure, and (b) is a schematic diagram of the microscopic morphology. It can be seen from the figure that the freeze-dried self-encapsulated foam material not only has a porous structure, but also has a core-shell structure. The microstructures of the shell layer and the core are significantly different, and this kind of skeleton core-shell structure is the fundamental reason for preventing polyethylene glycol leakage.

[0040] like Figure 4, are differential scanning calorimetry curves of the phase change materials prepared in Examples 1-5 and Comparative Examples 1-6 of the present invention, wherein (a) is the temperature rise diagram of Examples 1-5, (b) is the temperature drop diagram of Examples 1-5, (c) is the temperature rise diagram of Comparative Examples 1-6, and (d) is the temperature drop diagram of Comparative Examples 1-6. It can be seen from the figures that the phase change enthalpies of Examples 1-5 are 149.45 J / g, 154.32 J / g, 162.86 J / g, 173.68 J / g, and 184.49 J / g, respectively, and the phase change enthalpies of Comparative Examples 1-6 are 148.26 J / g, 140.34 J / g, 124.40 J / g, 114.27 J / g, 110.56 J / g, and 65.18 J / g, respectively. Although the phase change latent heat of the phase change materials prepared in Comparative Examples 1 and 2 is relatively high, both are unable to encapsulate polyethylene glycol and melt quickly at 100° C., and have no anti-leakage function, and therefore cannot be used.

[0041] like Figure 5 , is a differential scanning calorimetry graph of the solid-solid phase change material prepared in Example 1 of the present invention before and after 2000 thermal cycles. It can be seen from the figure that the positions of the comparison peaks after 1 cycle and 2000 cycles do not change much, and the integrated area hardly changes, indicating that the thermal stability is very good after 2000 cycles.

[0042] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein with equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the scope of protection of the claims of the present invention.

Claims

1. A method for preparing a two-component polysaccharide / polyethylene glycol solid-solid phase change material based on freeze-drying self-encapsulation, characterized in that: Follow the steps below in order: S1. Preparation of multi-component hydrogels After adding alginate and cellulose salt into water and mixing evenly, polyethylene glycol is added thereto, and after stirring at 50°C for 1 hour, a 1.2 mol / mL hydrochloric acid solution is added, and the pH value of the solution is adjusted to 3-5, and then the solution is aged at 40°C for 6-48 hours to obtain a multi-component hydrogel; S2. Preparation of porous foam material Freezing and cooling the multi-component hydrogel and then freeze-drying it to obtain a porous foam material; S3. Preparation of solid-solid phase change materials 0.1-0.2 g of the porous foam material was placed in a cylindrical metal mold with a diameter of 13 mm and pressed to obtain a two-component polysaccharide / polyethylene glycol solid-solid phase change material.

2. The method for preparing a two-component polysaccharide / polyethylene glycol solid-solid phase change material based on freeze-drying self-encapsulation according to claim 1, characterized in that: In step S1, the alginate is one or more of sodium alginate, potassium alginate, and calcium alginate; and the cellulose salt is sodium carboxymethyl cellulose or potassium carboxymethyl cellulose.

3. The method for preparing a two-component polysaccharide / polyethylene glycol solid-solid phase change material based on freeze-drying self-encapsulation according to claim 1, characterized in that: In step S1, the molecular weight of the polyethylene glycol is 2000-10000.

4. The method for preparing a two-component polysaccharide / polyethylene glycol solid-solid phase change material based on freeze-drying self-encapsulation according to claim 1, characterized in that: In step S1, the mass ratio of alginate to cellulose salt, water and polyethylene glycol is 1:(0.01-0.5):(20-100):(5-9).

5. The method for preparing a two-component polysaccharide / polyethylene glycol solid-solid phase change material based on freeze-drying self-encapsulation according to claim 1, characterized in that: In step S2, the freezing and cooling is performed according to the following procedure: (a) In the first cooling stage, the temperature was lowered from room temperature to 0 °C at a cooling rate of 0.3 °C / min and kept at this temperature for 6 h; (b) The second cooling stage: the temperature was lowered from 0°C to -20°C at a cooling rate of 0.1°C / min and kept warm for 18 h.

6. The method for preparing a two-component polysaccharide / polyethylene glycol solid-solid phase change material based on freeze-drying self-encapsulation according to claim 1, characterized in that: In step S2, the freeze-drying temperature is -60°C and the time is 20-60 h.

7. The method for preparing a two-component polysaccharide / polyethylene glycol solid-solid phase change material based on freeze-drying self-encapsulation according to claim 1, characterized in that: In step S3, the pressing process is: firstly, a load of 1-2 MPa is applied for pre-pressing, then a load of 5-10 MPa is applied for pressing, and the pressure is maintained for 10-50 s.

Citation Information

Patent Citations

  • Double-network phase change aerogel and preparation method thereof

    CN111187598A

  • Elastic aerogel and preparation method thereof

    CN114377187A

  • Aerogel heat insulation core material and high-performance aerogel composite heat insulation pad

    CN114516202A

  • A flexible insulating member

    WO2024254032A1